Futebol na era das arenas: o fechamento da coréia do beira-rio e a elitização dos estádios - Biazussi, Júlia Salvadego (2025)
Football, originally elitist, was progressively incorporated by the Brazilian popular classes, becoming a fundamental part of national identity. Even with institutionalization in stadiums, the sport remained alive in improvised spaces, such as floodplains and streets, resisting elitization. From the 1990s onwards, modernization and the increase in ticket prices promoted social exclusion, making stadiums less accessible environments for workers and students, especially with the elimination of popular sectors such as the Beira-Rio's "Korea" section. This process resulted in profound changes in the profile of fans and in the social dynamics of Brazilian football. Given the above, the study aims to analyze the process of elitization of stadiums, in particular the case of Beira-Rio. The methodology adopted in this study is bibliographic in nature. The research was conducted through a systematic literature review, focused on academic works and studies that address the topic. Scientific publications were considered, such as journal articles, theses, dissertations, and books, as well as documents that discuss the topic. The discussion of stadiums goes beyond architecture or ticket prices. Reflecting on this entire process, it becomes clear that the debate about the elitization of stadiums goes beyond the discussion of architecture or ticket prices. It is fundamentally a topic linked to citizenship, the right to the city, and the recognition of football as a collective and cultural heritage. It is essential that the development of new arenas and the adoption of modern practices go hand in hand with respect for the history of the clubs, the diversity of their fan bases, and the appreciation of the traditions that make Brazilian football a world reference.